Development of Student’s Mission Learning Media on The Addition and Subtraction of Integer - Nita Fatma Fauziah; Arum Sulistyo Pawestri (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
The success of the students in learning addition and subtraction of integer can be influenced by some factors, one of them is how the teacher delivering those materials. One of joyful learning in teaching addition and subtraction of integer is by using educational games. This research purpose is to develop a valid and practical learning media, which is called educational game "Student’s Mission for the fourth graders of junior high school in addition and subtraction of integer. The development model of tis research is adapted from Plomp Model that has four stages: (1) needs analysis, (2) designing stage, (3) realization stage, and (4) test, evaluation, and revision. Based on the data analysis, it was obtained that the learning media which is developed is valid and practical.